INFORMATION AND LANGUAGE FOR EFFECTIVE COMMUNICATION - Sammy Pitoy (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
Information and Language for Effective Communication (ILEC) is a language teaching approach emphasizing learnersâ extensive exposure in different language communicative sources. In ILEC, the language learners will first receive instructions of ILEC principles and application. Afterwards, they will receive autonomous, direct, purposeful, and intensive Input Exposure in particular source/s of information. This will be followed by an Output exposure, in which language learners are engaged in classroom actual discussion in English, analyzing information they have collected before. This article investigates the gradual development of learnersâ speaking fluency after undergoing autonomous exposure, which the author used as an effective English teaching innovation for the multi-level second language learners.